Glass, mineral and melt inclusion EMPA data for the Medieval eruptions (800-1240 AD) in the Reykjanes Peninsula, Iceland ... - Caracciolo, Alberto; Bali, Eniko; Halldórsson, Saemundur; Guðfinnsson, Guðmundur; Kahl, Maren; Þórðardóttir, Ingibjorg; Pálmadóttir, Guðrun; Silvestri, Valerio (Interdisciplinary Earth Data Alliance (IEDA), 2024)
The dataset contains EMPA major and minor element data of melt inclusions, glasses, olivine, clinopyroxene and plagiocalse minerals in the eruptive products from the 800-1240 AD Fires, the medieval eruptions in the Reykjanes Peninsula, Iceland. It also contains sulfur (S) and chlorine (Cl) analyses for melt inclusions and groundmass glasses.The dataset is published in Caracciolo et al. (2023), with volatiles publsihed in Caracciolo et al. (2024). ...